Association of HLA polymorphisms and acetaminophen-related Steven-Johnson syndrome with severe ocular complications in Thai population. Issue 6 (23rd November 2020) - Jongkhajornpong, Passara; Ueta, Mayumi; Lekhanont, Kaevalin; Puangsricharern, Vilavun; Prabhasawat, Pinnita; Chantaren, Patchima; Pisuchpen, Phattrawan; Kinoshita, Shigeru
Abstract : Background/aims: To investigate the association of genetic polymorphisms of human leucocyte antigens (HLA) class I and II genes with acetaminophen-related Steven-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) who developed severe ocular complications (SOC) in the Thai population. Methods: A prospective case–control study including 20 unrelated Thai acetaminophen-related SJS/TEN patients with SOC and 60 Thai healthy volunteers, recruited at three university hospitals in Bangkok, Thailand, from September 2014 to August 2019. HLA genes were analysed using PCR amplification followed by hybridisation with sequence-specific oligonucleotide (SSO) probes with bead-based typing kits. The carrier and gene frequencies of individual HLA alleles in patients were compared with those in control volunteers based on dominant assumption using Fisher's exact test. Results: Among HLA class I polymorphisms, HLA-A*33:03, HLA-B*44:03 and HLA-C*07:01 were significantly associated with acetaminophen-related SJS/TEN and SOC with high ORs (95% CI, corrected p value; Pc) in carrier frequency of 5.4 (1.8 to 16.3, Pc=0.0274), 9.0 (95% CI 2.7 to 30.4, Pc=0.0034), and 9.3 (2.8 to 30.2, Pc=0.0022), respectively. There were no significant HLA class II associations with the disease after corrected for a total number of alleles tested. Conclusion: HLA-B*44:03 was strongly associated with acetaminophen-related SJS/TEN patients who developed SOC in Thai population. In addition, we also found moderate to strong associations with HLA-A*33:03 and HLA-C*07:01 suggesting their potential roles in the pathogenesis of SOC in acetaminophen-related SJS/TEN.